2016
DOI: 10.1016/j.jhydrol.2016.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the integration of Soil Moisture Accounting into the NRCS-CN model

Abstract: Rainfall-runoff quantification is one of the most important tasks in both engineering and watershed management as it allows the identification, forecast and explanation of the watershed response. This non-linear process depends on the watershed antecedent conditions, which are commonly related to the initial soil moisture content. Although several studies have highlighted the relevance of soil moisture measures to improve flood modelling, the discussion is still open in the literature about the approach to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Alves (2016) comments that for CNI antecedent moisture conditions, initial abstraction values are higher because the soil is dry and water infi ltration is higher, which is not the case for the conditions CNII and CNIII. Durán-Barroso et al (2016) highlight that the SCS-CN method is very sensitive to the CN value, i.e., small variations of this parameter interfere considerably with maximum fl ows. This is because the CN value is directly related to factors that aff ect surface runoff , such as soil type, land use and occupation, and soil moisture.…”
Section: Maximum Observed and Estimated Flow For Diff Erent Return Periodsmentioning
confidence: 96%
“…Alves (2016) comments that for CNI antecedent moisture conditions, initial abstraction values are higher because the soil is dry and water infi ltration is higher, which is not the case for the conditions CNII and CNIII. Durán-Barroso et al (2016) highlight that the SCS-CN method is very sensitive to the CN value, i.e., small variations of this parameter interfere considerably with maximum fl ows. This is because the CN value is directly related to factors that aff ect surface runoff , such as soil type, land use and occupation, and soil moisture.…”
Section: Maximum Observed and Estimated Flow For Diff Erent Return Periodsmentioning
confidence: 96%
“…The evaluation proposed by Hawkins (1993) have been implemented in different parts of the world which had runoff observed data as USA (Hawkins, 1993;Durán-Barroso et al, 2016;Santikari & Murdoch, 2019), Argentina ), Mexico (Ibáñez-Castillo et al, 2014Pérez Nieto et al, 2015), Brasil (da Cunha et al, 2019Durán-Barroso et al, 2016) India (Gundalia & Dholakia, 2014;Lal et al, 2015Lal et al, , 2017Lal et al, , 2019 and South Korea (Ajmal et al, 2015); in all these studies a great difference between the CN of SCS-CN model and the CN derived from observed data was found, showing that SCS-CN method cannot calculate runoff properly.…”
Section: Introductionmentioning
confidence: 99%